Pt- and Pd-decorated MWCNTs for vapour and gas detection at room temperature - Baccar, Hamdi; Thamri, Atef; Clément, Pierrick; Llobet, Eduard; Abdelghani, Adnane (Beilstein Journal of Nanotechnology, 2015)
Here we report on the gas sensing properties of multiwalled carbon nanotubes decorated with sputtered Pt or Pd nanoparticles. Sputtering allows for an oxygen plasma treatment that removes amorphous carbon from the surface of the carbon nanotubes and creates oxygenated surface defects in which metal nanoparticles nucleate within a few minutes. The decoration with the 2 nm Pt or the 3 nm Pd nanoparticles is very homogeneous. This procedure is performed at the device level (i.e., for carbon nanotubes deposited onto sensor substrates) for many devices in one batch, which illustrates the scalability for the mass production of affordable nanosensors. The response to selected aromatic and non-aromatic volatile organic compounds, as well as pollutant gases has been studied. Pt- and Pd-decorated multiwalled carbon nanotubes show a fully reversible response to the non-aromatic volatile organic compounds tested when operated at room temperature. In contrast, these nanomaterials were not responsive to the aromatic compounds studied (measured at concentrations up to 50 ppm). Therefore, these sensors could be useful in a small, battery-operated alarm detector, for example, which is able to discriminate aromatic from non-aromatic volatile organic compounds in ambient.
Keywords: gas and vapour sensing; metal decoration; mutiwalled carbon nanotubes; plasma treatment; sputtering